A rare association of Takotsubo cardiomyopathy with neuroleptic malignant syndrome. Issue 2 (3rd March 2020) - Ullah, Waqas; Cheema, Muhammad Arslan; Ashfaq, Ammar; Mukhtar, Maryam; Ali, Zain; Ur Rashid, Mamoon; Figueredo, Vincent
ABSTRACT: Neuroleptic malignant syndrome is a potentially fatal neurological condition secondary to antipsychotic medication. It is characterized by distinctive clinical findings and autonomic disturbances. NMS has not been associated with Takotsubo cardiomyopathy (TCM). TCM is an abnormal response to physiological stressors resulting from the autonomic abnormalities which at times can mimic myocardial infarction (MI). We present a unique case of a 54-year-old female with bipolar disease presenting with lithium and haloperidol-induced NMS complicated by TCM. The purpose of this case is to make clinicians aware of this rare association.